2016
DOI: 10.1063/1.4962516
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of the intermolecular potential on the wetting properties of water on silica surfaces

Abstract: We study the wetting properties of water on silica surfaces using molecular dynamics (MD) simulations. To describe the intermolecular interaction between water and silica atoms, two types of interaction potential models are used: the standard Bródka and Zerda (BZ) model, and the Gulmen and Thompson (GT) model. We perform an in-depth analysis of the influence of the choice of the potential on the arrangement of the water molecules in partially filled pores and on top of silica slabs. We find that at moderate po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(103 reference statements)
1
5
0
Order By: Relevance
“…It is noted that in the validation simulation, the hydroxyl groups on the surface of silicon dioxide substrates are fixed as other representative works done. The measured contact angle is 7.8°, which is in good agreement with that in the work by Pafong et al [ 37 ]. They reported a water contact angle of 7.0°, which presents a relative deviation of only 10.3%.…”
Section: Methodssupporting
confidence: 91%
“…It is noted that in the validation simulation, the hydroxyl groups on the surface of silicon dioxide substrates are fixed as other representative works done. The measured contact angle is 7.8°, which is in good agreement with that in the work by Pafong et al [ 37 ]. They reported a water contact angle of 7.0°, which presents a relative deviation of only 10.3%.…”
Section: Methodssupporting
confidence: 91%
“…In Figure S6, it is shown that water molecules prefer to stay near the pore wall. 87 Furthermore, from Figures 7 and S5 a bilayer formation is assumed, as the length of the 1-octanol molecule is roughly 0.9 nm. Therefore, two layers of 1-octanol molecules that interact via their hydrophobic aliphatic chains may arrange inside the pore as illustrated schematically in Figure 6b.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the latter, we performed a simulation with only water and no 1-octanol in the pore at 15% pore filling. In Figure S6, it is shown that water molecules prefer to stay near the pore wall . Furthermore, from Figures and S5 a bilayer formation is assumed, as the length of the 1-octanol molecule is roughly 0.9 nm.…”
Section: Resultsmentioning
confidence: 99%
“…28 Our still crude model of hydrophilic surface is unable to catch these phenomena, and deserve further studies. Several directions are privileged: (i) considering more realistic amorphous silica surfaces, with a degree of hydroxylation closer to Vycor surfaces (16 OH/nm 2 ) 22 and possibly including disorder, [54][55][56] which favors the formation of clusters that are believed to play an important role; (ii) studying the effect of the geometry of the water/silica interface, since this is known to influence water properties, in particular in small pores; (iii) improving the water-silica interaction model, since it has been shown that the hydrophilic properties of silica are much more sensitive to the potential than the surface hydroxyl density; 44,97 and, (iv) improving the silica interatomic potential, in particular regarding the dynamics of the silanol groups interacting with water.…”
Section: Discussionmentioning
confidence: 99%